Date night - Twentieth Century-Fox Film Corporation; 21 Laps Entertainment (Firm).; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. 20th Century Fox Home Entertainment, 2006)
An ordinary couple is in the right place, on the wrong night. Phil and Claire Foster are a sensible, suburban husband and wife slogging through their daily lives and marriage. But a case of mistaken identity sets off an outrageous chain of events involving small-time thieves, big-city mobsters, corrupt cops and a crazed cabbie, as the Fosters' 'date night' turns into a wild ride they'll never forget!
Special features: audio commentary by director Shawn Levy (theatrical version only); alternate scenes; Directing off-camera featurette, Directing 301 featurette; public service announcements; gag reel.
Director of photography, Dean Semler ; editor, Dean Zimmerman ; music, Christophe Beck.
Steve Carell, Tina Fey, Taraji P. Henson, Jimmi Simpson, Common, William Fichtner, Mark Wahlberg, Mila Kunis.
Rating for theatrical version PG-13; for sexual and crude content throughout, language, some violence and a drug reference. Extended version not rated.
DVD videos, NTSC Region 1.
English, French or Spanish dialogue; English, French or Spanish subtitles; English subtitles for the deaf and hard of hearing; closed captioned except special features.
Keywords: Married people -- Drama; Criminals -- Drama; New York (N.Y.) -- Drama